2021
DOI: 10.1111/jph.13034
|View full text |Cite
|
Sign up to set email alerts
|

Wheat susceptibility to blast is enhanced by a photosynthetic inhibitor

Abstract: Considering blast, caused by Pyricularia oryzae, as a critical threat to wheat yield and the importance of photosynthesis as the source of energy used by plants to activate their mechanisms of defence to counteract pathogen infections, this study aimed to investigate whether wheat plants compromised in their photosynthetic process by using an inhibitor of photosynthesis could become more susceptible to blast. Plants from cultivars BRS 220 (moderately resistant) and BRS Guamirim (susceptible) were non‐sprayed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As known, studies demonstrated that pathogens secret their effectors for linking to receptor specifics in chloroplasts looking for a reduction drastic in the ROS controlling the plant defense mechanisms, suggesting the crucial role of the photosynthetic machinery in the basal plant resistance against pathogen infection [69]. In this sense, the manipulation of photosynthetic activity using photosynthesis inhibitor-specific (DCMU) in wheat cultivars with differential basal resistance to Pyricularia oryzae showed increases in the blast severity in both cultivars as a consequence of a low photosynthetic activity affecting the enzymatic responses related to plant resistance such as phenylalanine ammonia-lyase (PAL) and reinforced the concept that photosynthesis was important for wheat resistance to blast [70].…”
Section: Photosynthetic Alterations By Pathogen Infectionmentioning
confidence: 82%
“…As known, studies demonstrated that pathogens secret their effectors for linking to receptor specifics in chloroplasts looking for a reduction drastic in the ROS controlling the plant defense mechanisms, suggesting the crucial role of the photosynthetic machinery in the basal plant resistance against pathogen infection [69]. In this sense, the manipulation of photosynthetic activity using photosynthesis inhibitor-specific (DCMU) in wheat cultivars with differential basal resistance to Pyricularia oryzae showed increases in the blast severity in both cultivars as a consequence of a low photosynthetic activity affecting the enzymatic responses related to plant resistance such as phenylalanine ammonia-lyase (PAL) and reinforced the concept that photosynthesis was important for wheat resistance to blast [70].…”
Section: Photosynthetic Alterations By Pathogen Infectionmentioning
confidence: 82%
“…We hypothesized that the high expression of these photosynthetic genes in resistant trees helped to inhibit PWN infestation and delay the development of PWD in resistant P. thunbergii. For host-pathogen interactions, photosynthetic regulation was developed as an approach to seek to correlate functional manipulation of PS I and PS II with host defense responses derived from primary metabolism [43]. After PWN infestation, photosynthesisregulated genes responded first, followed by significant modifications in the circadian rhythm-plant pathway (p < 0.001).…”
Section: Potential Roles Of Photosynthesis In Resistance To Pwn In Pinementioning
confidence: 99%